Eco‐Friendly Alternative to Brining for Sustainable Storage of Table‐Olives Based on the Analyses Done with the Extracted Oil. Issue 8 (16th June 2021) - Ozilgen, Sibel; Aral, Selen; Ozilgen, Mustafa
Abstract: Degree of quality changes in coated and uncoated reference table olives are assed based on the analyses done with the extracted oil at different storage temperatures. The results reveal that storing the table olives after coating with chitosan reduces the product and embeds energy waste. Kinetic studies show that coating delays and slows down the lipid oxidation and decreases the maximum peroxide values attained. At all storage temperatures, the amounts of phenolics retained in the olives are significantly higher in the coated samples when compared with the uncoated references. The results show that coating may also raise the tolerable storage temperature by 14 °C. Coating 10% of the total global table oil production with chitosan may lead to up to 6720 MJ of storage energy savings and 546 t of less CO2 emissions into the atmosphere. Practical Applications : Coating olives with chitosan may improve the quality of the stored oils and reduce the energy requirement of the storage process and consequently reduce the amount of carbon dioxide emissions into the atmosphere compared to in‐brine storage method. Abstract : Coating olives with chitosan may improve the quality of the stored oils and reduce the energy requirement of the storage process and consequently reduce the amount of carbon dioxide emissions into the atmosphere compared to in‐brine storage method.